Treatment of acute abscesses in the casualty department. Issue 6332 (19th June 1982) - Simms, M H; Curran, F; Johnson, R A; Oates, J; Givel, J C; Chabloz, R; ALexander-Williams, J
Abstract : In the treatment of acute pyogenic soft-tissue abscess incision, curettage, and primary suture was compared with incision and drainage alone in a randomised prospective trial. Operations were performed under antibiotic cover by casualty officers, and patients were reviewed by an independent observer in a septic dressing clinic. Altogether 114 patients were studied, of whom 54 were treated by curettage and primary suture and 60 by simple drainage. The mean healing time was 8.9 days in those treated by primary suture and 7.8 days in those treated by simple drainage (p less than 0.05). Primary healing failed to occur in 19 (35%) of the sutured wounds, but there were no other complications in either group. It is concluded that incision and drainage alone is adequate treatment for acute soft-tissue abscess.